Orientation of Da'wah; Reinterpreting the Goals and Essence of Islamic Da'wah - Uliyah, Taqwatul (Westscience Press, 2025)
In recent times, Indonesian society has been filled with the phenomenon of loud preachers who continue to call for hate speech, slander, and hoaxes in the name of Islam. Not only non-Muslims, but also Muslims are afraid to see Islam. The theory of Islam that should have